PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI (KAHOOT) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIQIH KELAS VII DI MTS MUHAMMADIYAH 06 BANYUTENGAH TAHUN PELAJARAN 2020/2021 - Idzi Layyinnati; Nisa’atul Wahidah (Jurnal Pendidikan Islam, 2024)
This research is motivated by the increasing development of technologyin the era of the industrial revolution 4.0, educators can innovate learning tomake the learning process more interesting, namely by utilizing various programsthat can produce an interactive learning media. The lack of use of learning mediaused, especially in Fiqh learning, makes students' learning motivation decreaseand feel bored in the learning process which tends to use conventional methods.One of the latest application programs that can be used as interactive learningmedia is the Kahoot educational game application. The purpose of this study is todetermine whether there is an effect of application-based learning media(Kahoot) on student learning outcomes at MTs Muhammadiyah 06 Banyutengah.This study used a quantitative approach with a One-group pretest-posttest designand the number of respondents was 26 respondents, using sample data. Datacollection using pre-test and post-test questions. The collected data were analyzedby validity test, reliability test, normality test, homogeneity test, correlation test,significance test and coefficient of determination. Based on the results ofcalculations obtained manually with hypothesis testing using the product momentcorrelation formula, the results obtained rcount = 0.730> rtable = 0.3882. Whilefor the significance test, the results obtained tcount = 5.228> ttable = 2.063 atthe 5% significance level. From the discussion as mentioned, it can be concludedthat Ho is rejected and Ha is accepted or there is a positive and significantinfluence between Application-Based Learning Media (Kahoot) on StudentLearning Outcomes in Fiqh Class VII Subjects at MTs Muhammadiyah 06Banyutengah 2020/2021 Study Year